2016
DOI: 10.1111/joim.12565
|View full text |Cite
|
Sign up to set email alerts
|

Multiple rare genetic variants co‐segregating with familial IgA nephropathy all act within a single immune‐related network

Abstract: BackgroundIgA nephropathy (IgAN) is a common complex disease with a strong genetic involvement. We aimed to identify novel, rare, highly penetrant risk variants combining family‐based linkage analysis with whole‐exome sequencing (WES).MethodsLinkage analysis of 16 kindreds of South Italian ancestry was performed using an ‘affected‐only’ strategy. Eight most informative trios composed of two familial cases and an intrafamilial control were selected for WES. High‐priority variants in linked regions were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The role of MAPK and PI3K/Akt signalling on IgAN's pathophysiology have been described in previous studies (38)(39)(40)(41) . We therefore focussed on validating key components of the TGF-β and Wnt signaling pathways with less literature support and where CARNIVAL and GSEA provided opposite results.…”
Section: Fluorescence Immunohistology Detection Of Rhoa and β-Cateninmentioning
confidence: 83%
“…The role of MAPK and PI3K/Akt signalling on IgAN's pathophysiology have been described in previous studies (38)(39)(40)(41) . We therefore focussed on validating key components of the TGF-β and Wnt signaling pathways with less literature support and where CARNIVAL and GSEA provided opposite results.…”
Section: Fluorescence Immunohistology Detection Of Rhoa and β-Cateninmentioning
confidence: 83%
“…Cox et al identified 23 genes with candidate pathogenic variants functionally related to a large network of immune-related pathways. They speculated that the IgAN disease status may be affected by a series of mutations that affect immune-related networks (25). Milillo et al identified the SPRY2 gene related to IgAN, which is part of the MAPK/ERK pathway (26).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple rare variants participating in a common network can influence disease susceptibility. Future investigations might explore the development of combined biomarkers to generate a prognostic model which can usher into potential genomic biomarkers and drug targets for personalized therapy [58] .…”
Section: Iga Nephropathymentioning
confidence: 99%